Determine the best travel website service quality using Fuzzy TOPSIS approach / Nurul Suhada Aziz ... [et al.] - Aziz, Nurul Suhada; Idris, Nurul Fatihah; Khairudin, Nur Diini Afiqah; Muhamad Amin, Maznah Amirah (Unit Penerbitan UiTM Kelantan, 2020)
One of the crucial things to make a travel plan is to choose the best travel website quality. This is because there are many travel website that provides diverse services with different prices and many more. Therefore, it is important to make the right decision about choosing a travel website. This study implements Fuzzy TOPSIS to determine the best travel website quality. There are many factors that influence users’ selection such as responsiveness, efficiency and privacy and the best travel websites choose were Traveloka, Skyscanner and Expedia. Decision-makers are asked to rank these factors from very high (VH) to very low (VL) for QA weight, while for alternatives assessment from very good (VG) to very poor (VP); very high and very good specifies the most influencing factors while very low and very poor indicates the least influencing factors. Next, each data ranking transforms into matrix form. Then, calculate a Normalized Decision Matrix (NDM). Furthermore, calculate the weighted (NDM) and distance of each alternative from the worse condition (A ) and the best condition (A+). Lastly, calculate the closeness of the coefficient of each alternative and rank them. The higher the value of relative closeness, the higher the ranking order has the best travel website service quality that can satisfy consumer’s preferences.